PCR technology : (CRC Press, Taylor & Francis, 2013)
A technique used to amplify the number of copies of a specific region of DNA, the polymerase chain reaction (PCR) is at the forefront of the dramatic development of biochemistry. This text provides the tools for developing innovative approaches to using this leading technology. It includes theoretical considerations, discussions, and a selection of state-of-the-art techniques for mutation studies, clinical diagnosis, and the detection of food-borne pathogens. This edition also discusses the preparation of PCR experiments, includes examples of analytical PCR divided into qualitative and quantitative applications, and explores preparative methods that address DNA generation for further analysis and in vitro evolution